The association between self-report and behavioural measure of attentional control: Evidence of no relationship between ACS scores and antisaccade performance. (January 2022) - Todd, Jemma; Notebaert, Lies; Clarke, Patrick J.F.
Abstract: Attentional control theory proposes a relationship between poor attentional control and heightened anxiety vulnerability. While attentional control is often assessed via self-report, it is unclear to what extent self-report measures indicate attentional control abilities. This study sought to determine the relationship between questionnaire and behavioural measures of attentional control, and to examine their association with psychological symptoms. A well-powered non-clinical sample ( N = 207) completed the Attentional Control Scale (ACS) and measures of psychological symptoms (depression, anxiety, stress), as well as the antisaccade task as a behavioural measure of attentional control. Antisaccade performance was associated with both anxiety ( r = −0.187) and stress ( r = −0.195). ACS scores also correlated with all measures of psychological distress ( r = −0.248 to −0.459). However, there was no evidence for an association between ACS scores and antisaccade performance ( r = 0.027 to 0.110). Bayesian analyses indicated moderate to strong evidence that the null hypothesis is true (B10 = 0.094 to 0.302), suggesting an absence of an association. The present study is consistent with growing evidence that self-reported measures of attentional control may better reflect beliefs about attentional control abilities, highlighting the importance of selecting appropriate measures of the intended construct when researching individual differences in attentional control.